Integration of FMEA and TOPSIS for OHS Risk Mitigation Strategy in Lathe Machining Activities : Case Study in PT. SPPA - Lina Dianati Fathimahhayati; Fahreza Dwi Witriyan (Universitas Mercu Buana, 2023)
The machining process in PT. SPPA is still carried out conventionally, especially in the idler rebuilding process. There are found work accidents that result in work-related illnesses. In preventing accidents, it is necessary to do risk management efforts. Therefore it is necessary to conduct research by integrating FMEA and TOPSIS for risk management strategies in Occupational Health and Safety (OHS). The FMEA method is used to identify risks and assess the level of risk based on severity, ooccurrence and detection. Furthermore, the TOPSIS method is used to determine the order of priority for improvement to overcome existing risks. The results showed that there were 17 risks in machining activities with a lathe where the risks with the highest RPN value were experiencing pain or muscle cramps when setting up the lathe, experiencing noise during the lathe process, and exposure to chips from the lathe process. Furthermore, each risk is investigated using the 5 Whys method to determine the root causes of the problems, and it was found that the causes of these risks were low-quality work equipment, lack of training, socialization or briefings on OHS, and the high cost of providing adequate PPE. Based on these issues, a priority list of recommendations for improvement is compiled using the TOPSIS method, including routine equipment condition checks, providing SOPs for equipment use, providing appropriate PPE for each job, providing training for employees, allowing adequate rest time, and providing high-quality work equipment.